2000
DOI: 10.1007/s002530051666
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mediator demand - a novel rapid alternative for measuring biochemical oxygen demand

Abstract: The biochemical oxygen demand (BOD) test (BOD5) is a crucial environmental index for monitoring organic pollutants in waste water but is limited by the 5-day requirement for completing the test. We have optimised a rapid microbial technique for measuring the BOD of a standard BOD5 substrate (150 mg glucose/l, 150 mg glutamic acid/l) by quantifying an equivalent biochemical mediator demand in the absence of oxygen. Elevated concentrations of Escherichia coli were incubated with an excess of redox mediator, pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 10 publications
3
52
0
2
Order By: Relevance
“…For BOD 60 , like C, the influence of N becomes less significant (Table 5). The latter implies that besides C and N, other factors, particularly the types of microbes present (Karube et al 1977b;Pasco et al 2000;Shrivastava et al 2000), could play dominant roles in influencing long-term BOD.…”
Section: Bod Kineticsmentioning
confidence: 97%
See 1 more Smart Citation
“…For BOD 60 , like C, the influence of N becomes less significant (Table 5). The latter implies that besides C and N, other factors, particularly the types of microbes present (Karube et al 1977b;Pasco et al 2000;Shrivastava et al 2000), could play dominant roles in influencing long-term BOD.…”
Section: Bod Kineticsmentioning
confidence: 97%
“…The test results are variable and are often difficult to reproduce (Constable and McBean 1977). Further studies revealed that variability in samples resulting from factors such as pH, temperature, initial dissolved oxygen, nutrients, toxic substances, and types of microbes present could affect the reliability of the test (Karube et al 1977b;Pasco et al 2000;Shrivastava et al 2000). In addition to the variability associated with the test results, the conventional BOD measurement methods are also labor intensive and time consuming.…”
Section: Introductionmentioning
confidence: 97%
“…특히 수질의 화학적 산소요구량(chemical oxygen demand; COD)의 빠르고 정확 한 측정의 중요성은 더욱 크게 부각되고 있으며, COD는 수질 오염 여부를 판단하는 다른 지표들에 비해 그 측정가능 범위와 적용범위가 넓고, 하 ․ 폐수처리와 환경정화 분야에 깊이 관여 되어 환경정책을 결정하는 매우 중요한 지표로써 이용되고 있다 (3) . 생화학적 산소요구량(biochemical oxygen demand; BOD) 과 더불어 화학적 산소요구량은 환경수질 시료의 오염도 파악 에 매우 중요한 인자 중 하나다 (4) . COD는 수질 시료 중에 포함 된 유기화합물과 일부 무기화합물을 화학적으로 분해시킬 때 필요로 하는 산소 요구량으로서 호수, 하천 , 하수 및 산업 폐수 등의 오염 척도로 사용된다 (5) .…”
Section: 서 론unclassified
“…12,13 In such sensors, while the bacteria metabolize organic species in the sample, the mediators act as electron acceptors for the microbial redox reactions rather than oxygen, and the reduced mediators are then detected electrochemically upon reoxidation at an electrode. Using potassium ferricyanide (K 3 [Fe(CN) 6 ]) as a redox mediator, it was possible to determine BOD even in anaerobic samples.…”
Section: −11mentioning
confidence: 99%